2021
DOI: 10.1371/journal.pone.0248968
|View full text |Cite
|
Sign up to set email alerts
|

The experience of care partners of patients with Parkinson’s disease psychosis

Abstract: Background Parkinson’s disease psychosis (PDP) has a major impact on quality of life and care partner burden; however, little is known about the lived experiences of care partners in managing PDP. Objective To understand how care partners of individuals with PDP experience their role and articulate their needs related to psychosis. Methods This was a qualitative study of semi-structured telephone interviews. Recruitment was conducted online via the clinical study matching tool, Fox Trial Finder; study acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…A study of the caregiving experience for someone with PD psychosis found that coping could be improved if carers had assistance to process feelings associated with their loved ones' PD psychosis. A recent study found that care partners of PWP and psychosis often discussed burden and guilt, triggers to psychosis and strategies to care for loved ones with psychosis [28]. Three participants in this study experienced jealous delusions.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…A study of the caregiving experience for someone with PD psychosis found that coping could be improved if carers had assistance to process feelings associated with their loved ones' PD psychosis. A recent study found that care partners of PWP and psychosis often discussed burden and guilt, triggers to psychosis and strategies to care for loved ones with psychosis [28]. Three participants in this study experienced jealous delusions.…”
Section: Introductionmentioning
confidence: 62%
“…Three participants in this study experienced jealous delusions. Challenging emotions and consequences included anger, lowered mood, stress, loss of social networks and diminished self-esteem [28]. Other work documented the mental health and relational problems for carers of psychotic persons, not specifically PD [29].…”
Section: Introductionmentioning
confidence: 99%
“…Progression of non-motor symptoms of PD does not necessarily follow motor deterioration 24 and, given the burden non-motor symptoms pose on PwP 8 , 9 and caregivers, 10 , 11 increased attention towards prompt recognition and treatment of non-motor symptoms during the COVID-19 pandemic is warranted. PwP were generally less likely than CP proxies to report increased PD symptoms, but the difference was particularly prominent for non-motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Non-motor symptoms of PD profoundly add to caregiver burden, adversely affect caregivers’ mental health, 10 , 11 , 30 , 31 and are associated with a reduced CP satisfaction from their relationship with the PwP. 32 The increase in delusions and hallucinations reported by PwP in this survey are particularly worrisome, since, in addition to frequent hospitalizations and falls, 33 it is these symptoms that have been found to be the main reason for placement in a long-term care facility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation